Role of Mast Cells in the Pathogenesis of Pruritus in Mastocytosis - Dominika Kwiatkowska; Adam Reich (Medical Journals Sweden, 2021)
Pruritus can be defined as an unpleasant sensation that evokes a desire to scratch and significantly impairs patients' quality of life. Pruritus is widely observed in many dermatoses, including mastocytosis, a rare disease characterized by abnormal accumulation of mast cells, which can involve skin, bone marrow, and other organs. Increasing evidence highlights the role of mast cells in neurogenic inflammation and itching. Mast cells release various pruritogenic mediators, initiating subsequent mutual communication with specific nociceptors on sensory nerve fibres. Among important mediators released by mast cells that induce pruritus, one can distinguish histamine, serotonin, proteases, as well as various cytokines. During neuronal-induced inflammation, mast cells may respond to numerous mediators, including neuropeptides, such as substance P, neurokinin A, calcitonin gene-related peptide, endothelin 1, and nerve growth factor. Currently, treatment of pruritus in mastocytosis is focused on alleviating the effects of mediators secreted by mast cells. However, a deeper understanding of the intricacies of the neurobiology of this disease could help to provide better treatment options for patients.